TINGKAT KEPUASAN PASIEN TERHADAP PELAYANAN KESEHATAN DENGAN MODEL SIKDA OPTIMA DIPUSKESMAS JAYA MUKTI TAHUN 2016 - Imelda " "; Darim " Karim; Bayhakki " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractSIKDA Optima was aregional health information system that’s designed to meet various minimum requirements needed in the area of health information processing. SIKDA Optima is designed to become the standard for local governments in the management of health information in the region. This study aims to determine the level of patient satisfaction with health services at the Public Health Center Jaya Mukti. Design of study used is descriptive conducted in Public Health Center Jaya Mukti Dumai City. Sample of study was 100 respondents drawn using simple random sampling. The research was done by using questionnaire that had been tasted it’s validity and reliability. The analysis is a univariate analysis with the results of the level of patient satisfaction with health care model SIKDA Optima in the Public Health Center Jaya Mukti showed that 79.36 is Good that respondents were satisfied. The results are consistent with the intended use of the SIKDA Optima application that the administration can be felt both by society and by the officer as the provider, because the waiting time of patients is reduced, the flow more clearly and reduce the administrative burden of health workers so that services become more effective and efficient. The results of this study recommend for health workers, especially nurses to improve patient satisfaction in other Public Health Centers linked to patient satisfaction with health care model Optima SIKDA.